2010
DOI: 10.1007/s00213-010-2134-y
|View full text |Cite
|
Sign up to set email alerts
|

Chronic treatment with fluoxetine prevents the return of extinguished auditory-cued conditioned fear

Abstract: These data extend our previous findings and suggest that chronic fluoxetine treatment favor extinction memory by dampening the reactivation of the original tone-shock association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…However, chronic fluoxetine may also prevent return of extinguished fear and facilitate extinction in female rats (3032). Ultimately, an effect of chronic SSRI administration on extinction, as well as SSRI efficacy for treatment of depression and PTSD, may be driven by a change in glutamatergic transmission, as supported by recent DCS and ketamine findings.…”
Section: Pharmacotherapy Approaches To Fear- and Anxiety-related Disomentioning
confidence: 99%
“…However, chronic fluoxetine may also prevent return of extinguished fear and facilitate extinction in female rats (3032). Ultimately, an effect of chronic SSRI administration on extinction, as well as SSRI efficacy for treatment of depression and PTSD, may be driven by a change in glutamatergic transmission, as supported by recent DCS and ketamine findings.…”
Section: Pharmacotherapy Approaches To Fear- and Anxiety-related Disomentioning
confidence: 99%
“…Administration of SSRIs is a common pharmacological approach to the treatment of mood and anxiety disorders including panic disorder. Recent studies indicate that chronic administration of the SSRI fluoxetine improves extinction retention (22)(23)(24), suggesting a potential mechanism underlying its anxiolytic and antidepressant effects (25). Here, we test whether fluoxetine alters the 5-HTT DPF, which would further implicate the 5-HTT DPF as a mediator of both altered extinction retention and the therapeutic effects of SSRIs.…”
Section: Genetic Variation In 5-htt Polyadenylation Selectively Modulmentioning
confidence: 99%
“…To further relate the 5-HTT distal polyadenylation fraction to anxiety-related emotional processing, we treated mice with the selective serotonin reuptake inhibitor (SSRI) fluoxetine, a treatment that facilitates extinction retention (22)(23)(24), alleviates anxiety and depressive symptoms (25), and is the most commonly used pharmacological treatment for panic disorder. Chronic fluoxetine increased the 5-HTT DPF in mouse brain, suggesting that biological factors that increase the 5-HTT DPF are anxiolytic and those that decrease it are anxiogenic.…”
mentioning
confidence: 99%
“…The effect of antidepressants as enhancers of fear extinction, however, is still matter of debate. Some animal studies found facilitated extinction or extinction retention with chronic use of antidepressants [93][94][95] albeit it has not been always replicated 96 perhaps due to sex-related differences 97 . One small human study found that chronic use of antidepressants may enhance extinction although it is not clear that the BDNF pathway is the one responsible for such effects 98 .…”
Section: Discussionmentioning
confidence: 99%